The intermicrovillar adhesion complex in gut barrier function and inflammation - Bernadette Mödl; Katy Schmidt; Doris Moser; Robert Eferl (Exploration of Digestive Diseases, 2022)
The surface of intestinal epithelial cells is covered by the brush border, which consists of densely packed cellular extrusions called microvilli. Until recently, microvilli have not been known to be interconnected. In 2014, a protein complex, called the intermicrovillar adhesion complex (IMAC) which is located at the tips of the microvilli and responsible for the regular spatial organization of the brush border, was identified. Deletion of IMAC components such as cadherin-related family member-2 (CDHR2) in mice resulted in microvillus disorganization and fanning, a structural aberration that is also found in the brush border of patients with inflammatory bowel disease. The etiology of inflammatory bowel disease has been primarily associated with dysfunctional mucosal immunity, but the discovery of the IMAC may encourage theories of an epithelial origin. Here, possible effects of the brush border on the gut barrier function and intestinal inflammation are discussed proposing that the IMAC protects against inflammation through its microvillus cross-linking function.